RELIABILITY OF VEHICLE VEHICLES AT THE STAGE OF PREPARATION (World Science, 2022)
The reduction of the duration of running-in is most strongly influenced by the speed-power and technological factors. It was experimentally established that at specific loads of 0.15 – 3 MPa and tribopair velocities of 6 – 40 m/min (0.1 - 0.66 m/sec) and methods of surface hardening and surface hardening, nitrocementation and ion-plasma thermocyclic nitriding, a combination of speed, power and technological factors can reduce the running-in process by 1.5 - 2 times.A mathematical model has been developed that combines the components of these factors for the running-in process in relation to the reduction of the latter.The stand for experimental research of the tribotechnical system, which consists of an automatic gearbox with a magnetic brake, a power supply, a control panel and a PC, has been upgraded. The firmware is written in the Python programming language.For further research in the chosen direction, the application of wear-resistant coatings with a thickness of 3 … 10 μm by PVD methods containing nitrides and carbides is promising.